HUMOR PADA GURU BERDASARKAN TINJAUAN PSIKOLOGI ULAYAT - Cindy Kashamira; Shanty Sudarji (Psibernetika, 2013)
Humor has become part of Indonesian society . The emergence of humor in almost every aspect of people's lives due to the role of humor in the life of a society that has a central role in human life, namely as a means of entertainment and education to improve the quality of human life. One of the benefits of humor is humor can play an important role in helping the learning process . The purpose of this study was to determine the teachers' humor in Jakarta based Communal Psychology Review . The research method used in this paper is a descriptive qualitative research method using the approach of Communal Psychology . This study begins with a Focus Group Discussion ( FGD ) and will be examined by using the Open -Ended Questionnaire ( OEQ ) . Based on the results of the study found that teachers tend to enjoy aggressive humor . However, in its application , teachers tend to use self -enhancing humor . In accordance with the results of the study found that the teachers also tend to not like to be used by the humorous material by another and vice versa . With a knowing sense of humor , the benefits of humor , humor style , one must know when the right time to catapult humor , so as not to hurt the feelings of others . With the penilitian about humor at teachers based on a review of Communal Psychology is expected to enrich the literature on Communal Psychology as a reference for subsequent indigenous research . Keywords: teachers , humor , psychology customary